KAJIAN LITERATUR PENGARUH INSEKTISIDA NABATI DAN INSEKTISIDA SINTETIK TERHADAP KEMATIAN LARVA NYAMUK AEDES AEGYPTI - Anindya Wahyu Utami; Mitoriana Porusia (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Currently, the larvicidal material that is still in great demand by the public is using synthetic insecticides. However, if it is used continuously with inappropriate doses it can cause several negative impacts such as larval resistance, environmental problems, and death of non-target organisms. Based on these negative impacts, many studies are currently examining the use of vegetable insecticides as a substitute for synthetic insecticides. This literature review aims to describe methods, review articles, and compare the results of the differences in each study related to control with vegetable insecticides and synthetic insecticides. The research method is carried out by summarizing selected journals, analyzing, and drawing conclusions. The results of this study in the literature review showed that the leaf extract of the seagrass C. serrullata was the most effective compared to the ethanol extract of bitter melon. The results of the probit analysis of the two showed that in killing 90% of the test larvae, the leaf extract of seagrass C. serrullata was able to kill at the lowest concentration (0.1675 mg/L) while the ethanol extract of bitter melon required the highest concentration (27,590 mg/L). ). Meanwhile, temephos still has the most potential in killing larvae. However, plant extracts can also potentially compete with temephos but should be at higher concentrations. Although currently temephos is still more potent than plant extracts, resistance to temephos has also been found in several areas.